IMPLEMENTASI PROGRAM ASISTENSI PENYANDANG DISABILITAS BERAT (ASPDB) DI DINAS SOSIAL KABUPATEN GORONTALO UTARA - Umar Sako Baderan; Rian Mohamad (STISIPOL Mujahidin Buol, 2023)
This study aims: to find out how the Implementation of the Assistance Program for Persons with Severe Disabilities (ASPDB) in the Social Service Office of North Gorontalo Regency. The research method uses a qualitative approach with a descriptive type of research. The results of the study found that the implementation of the ASPDB program in Kwandang District, Gorontalo Regency has not been carried out properly, this is because in terms of the number of Human Resources (HR) who carry out the program is not enough so that it cannot handle almost all areas in the sub-district. In addition, it was found that the replacement of participants who died was so long because they had to wait for a Decree from the Ministry of Social Affairs so that this could affect in renewing program participation. In addition, what is obtained is that the process of disbursement of funds for this program is not always on time because it also has to wait for instructions from the center and of course because of disbursement through banks, this can also affect the timeliness of funds to reach the hands of program participants.